Platelet Distribution Width Level in Patients With Systemic Lupus Erythematosus-Associated Pulmonary Arterial Hypertension and Its Diagnostic Value - Yuzhu HE; Yikai YU; Shaoxian HU (Archives of Rheumatology, 2020)
Objectives: This study aims to compare the platelet distribution width (PDW) level in patients with systemic lupus erythematosus-associated pulmonary arterial hypertension (SLE-PAH) with that in patients with systemic lupus erythematosus alone (SLE-non-PAH) and to evaluate the clinical value of the PDW level in the early diagnosis of SLE-PAH. Patients and methods: We analyzed 80 SLE-PAH patients (1 males, 79 females; 34.9±12.3 years; range, 19 to 77 years) and 154 sex- and age-matched SLE-non-PAH patients (4 males, 150 females; mean age 36.7±12.4 years; range, 19 to 69 years) hospitalized between June 2011 and April 2018. All patients underwent transthoracic Doppler echocardiography within three months of inclusion in the study. Age, sex, disease course, currently prescribed medications, clinical manifestations, and past history were collected. Pulmonary artery systolic pressure, ejection fraction, white blood cell count, red blood cell count, hemoglobin, platelet count, PDW, mean platelet volume, erythrocyte sedimentation rate, complement 3 (C3), and C4 levels were also obtained. Results: The PDW level was higher in the SLE-PAH group than that in the SLE-non-PAH group (p=0.023). SLE patients were allocated into high systemic lupus erythematosus disease activity index (SLEDAI) group (SLEDAI score, ≥10) (n=121) or low SLEDAI group (SLEDAI score, <10) (n=113). The PDW level was significantly higher in the high SLEDAI group than that in the low SLEDAI group (p=0.030). The receiver operating characteristic curve was used to evaluate the clinical value of the PDW level in diagnosing PAH in SLE patients. The PDW level was valuable for diagnosing PAH in SLE patients [area under the curve (AUC)=0.591, p=0.023]. The optimal critical value of the PDW level was 14.55 fL. Under these conditions, the sensitivity, specificity, and Youden index were 57%, 63% and 0.20, respectively. For newly diagnosed patients, the PDW level had good diagnostic accuracy, with an AUC of 0.626 (p=0.037). The optimal critical value of the PDW level was 14.65 fL. Under these conditions, the sensitivity, specificity, and Youden index were 66%, 67% and 0.33, respectively. Conclusion: The PDW level is a good predictor of SLE-PAH, and this parameter is applicable to various clinical settings.